Health seeking behavior in Bulak Banteng, Surabaya - Fatati Larasati (Intelektual Pustaka Media Utama, 2020)
Infant and under-five mortality rate in the world is still a major health problem that must be resolved immediately. Mother’s health seeking behavior very important to manage the health of his children. Purpose of this study was to investigate health seeking behavior among mothers when their children were sick. This study was descriptive quantitative involved 50 respondents. The results show majority mothers choose to take action when their children are sick with most choosing to take them to health care facilities and do their own treatment. Mothers are expected to always care for their children well and not too late for giving treatment when their children are sick.